New records of pteridophytes in summit region of Gunung Ledang, Johor - Z., Shahruddin; Go, Rusea; Zulkifli, Syaizwan Zahmir (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
Gunung Ledang or Mount Ophir is the highest peak of the southern Peninsular Malaysia and gazzeted as Johor National Parks. Studies on pteridophytes flora and diversity in Gunung Ledang, Johor has been done several times but none was documented validly except from Ridley, 1901. The objective of this study is to study the diversity of pteridophytes and prepare preliminary checklist of pteridophytes in the summit region of Gunung Ledang. Several field works had been carried out in November 2015 to January 2016, and five plots (20 m x 20 m) that systematically developed at different locations based on the wind direction (north, south, east, and west and peak of the mountain). A total of 27 species under 16 families and 21 genera were identified and recorded. The largest family is Gleicheinaceae (four species), followed by Sellaginellaceae and Pteridaceae (three species). Majority of pteridophytes are terrestrial (85%) while the remaining 11% are epiphytes and 4% are litophytes. Plot C (south) is the higher richness of pteridophytes with 11 species. Comparison with previous records revealed there are 16 species as new records of Gunung Ledang. One species found is Taenitis dimorpha, which is endemic to Peninsular Malaysia. As this study reveals a total of 16 new records and an edermic species, therefore it is essential for Taman Negara Gunung Ledang to systematically and comprehensively study its pteridophytes flora so that its true status could be identified.